Education in The Implementation of Yoga Exercises in Reducing Back Pain In The Third Trimester of Pregnant Women - Saputri, Ika Nur; Nurianti, Irma; Octavariny, Raisha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Back pain is a disorder that occurs during pregnancy and in various regions in Indonesia 60-80% of pregnant women experience back pain. Mothers with back pain during pregnancy have a higher risk of experiencing a longer duration of labor and emergency caesarean section. Back pain arises due to physical and hormonal changes as the gestational age increases, the uterus gets bigger and the flexibility of the back muscles decreases. The action taken to reduce back pain is prenatal yoga, which aims to make pregnant women able to adjust their posture and reduce back pain. This PkM aims to make PkM participants able to reduce the back pain of pregnant women. PkM activities were held on March 31, 2023 at PMB Nining Lubuk Pakam with PkM participants being pregnant women with Low Back Pain as many as 10 respondents. The PkM implementation method is the lecture and demonstration method. This activity was carried out at PMB Nining Lubuk Pakam. Education This prenatal yoga class is carried out through demonstrations, lectures, and questions and answers. Prenatal yoga exercises can reduce lower back pain in pregnant women at PMB Nining. Pregnant women should choose prenatal yoga to suppress back pain, especially in the face of labor with an intensity of once per week. As many as 90% of pregnant women feel satisfied after participating in prenatal yoga classes and there are 80% of mothers who feel their back pain has reduced. The conclusion is that prenatal yoga can be an alternative to choose in suppressing back pain in pregnant women.